ETHICAL PROBLEM OF EUGENICS AND BIOETHICS - Esnazarova, Zulfiya Baltashovna (SCIENCE and SOCIETY, 2026)
The article discusses ethical issues arising at the intersection of eugenics and bioethics in the context of modern scientific and technological development. The author analyzes the historical origins of eugenics, its transformation in the era of genetic engineering and biotechnology, and draws attention to the risk of human rights violations arising from interference with human genetics. Special attention is being paid to bioethical principles - personal dignity, autonomy of will, and the prevention of harm and injustice. The work emphasizes the necessity of ethical oversight of the development of biomedical technologies to preserve human values and prevent past mistakes. The theoretical and methodological basis of the research consists of bioethical, historical-genetic, and comparative analysis methods.
Keywords: eugenics; bioethics; ethical problem; human rights; genetic engineering; humanism; ethics; biophilosophy